Molecular cloning and characterization of transcripts encoding terpene synthase genes from Aquilaria malaccensis Lam - Wong, Mun Theng (2017)
Aquilaria malaccensis Lam. is an endangered tropical tree that produces agarwood, a natural product well-known for its fragrance and medicinal properties, in response to external stimuli. Agarwood contains a wide variety of terpenes and phenylethyl chromone derivatives. However, sesquiterpene was the only terpene synthase (TPS) gene that was being studied in Aquilaria. Therefore, both monoterpene and diterpene synthase genes which are equally important as sesquiterpene in agarwood formation from A. malaccensis were identified in this study. The aim of this study described here was to determine candidate TPS transcripts from A. malaccensis stems, to analyze the transcript expression profile in different tissues of A. malaccensis and then use this information to express terpene synthase in an Escherichia coli expression system. Using an in-house transcriptome assembled from A. malaccensis RNA sequencing project, specific primers targeted for TPS genes were designed. Three TPS candidate genes were selected based on their sequence similarities to other known plant TPSs and named AmTPS01, AmTPS02 and AmTPS03. The partial-length and full-length cDNAs were amplified from stem tissues using the RACE approach and cloned into the pSTBlue-1 vector. Only AmTPS03 is a full-length cDNA (3027 nucleotides), while the AmTPS01 and AmTPS02 sequences included only the 3’-ends (2014 and 1601 nucleotides, respectively). Gene annotation analysis indicates that the deduced peptide sequences of AmTPS01, AmTPS02 and AmTPS03 had 603, 421 and 786 amino acids, respectively. BLAST searches against the GenBank revealed that AmTPS01 had 72% similarity to myrcene synthase from Morus notabilis, AmTPS02 to 3R-linalool synthase from Theobroma cacao (62%) and AmTPS03 to ent-kaurene synthase from Castanea mollissima (81%). From phylogenetic analyzes, the three TPSs are found clustered within the functional homologs of the terpene synthase subfamilies. AmTPS01 and AmTPS02 are clustered with the monoterpene Tps-b subfamily, while AmTPS03 with the diterpene Tps-e subfamily. For the transcript expression analysis, qPCR experiments were carried out using different tissues and treatments. In tissue culture plantlets of A. malaccensis, AmTPS01 and AmTPS02 transcripts were highly expressed in the roots and stems, respectively, compared to leaves. The preference of expression in wood tissues is supported from the experiment using nursery-grown tree, where AmTPS02 also showed high expression in both stem (450-fold) and roots (100-fold) compared to leaves, while AmTPS01 showed the highest expression in stem (10-folds). AmTPS01 and AmTPS02 in calli responded to methyl jasmonate (MJ), a known trigger to production of fragrance constituents in agarwood with the highest expression detected 6 hours after treatment. Drill-wounding and application of a liquid inducer were carried out on plantation trees in a time-course experiment (0, 2, 4, 6, 12 and 24 hours). The liquid inducer apparently induced expression of AmTPS01 (4 hours) and AmTPS03 (6 hours) to the highest level (10-30-folds) compared to drill-wounding. AmTPS03 transcript was abundant in induced-plantation trees but was lowly expressed in MJ-treated calluses, tissue culture plantlets and nursery-grown trees, suggesting its expression is related to the tree’s physiological age and a strong inducer. To functionally characterize the three genes, the ORFs were ligated into pET-28a vector and expressed in the Escherichia coli BL21 (DE3) strain. Expression of the three His-tag fused proteins, AmTPS01 (70.90 kDA), AmTPS02 (50.29 kDa) and AmTPS03 (90.55 kDa) in bacteria resulted in the accumulation of the protein in insoluble forms. In conclusion, the cloned A. malaccensis TPS genes are wood-specific and respond differently to triggers of agarwood induction. In future, studies should be conducted to understand their actual roles in transforming basic isoprene building blocks into terpene compounds. This study provides a foundation for further elucidating the role of TPS genes in the biosynthesis of agarwood compounds in A. malaccensis.